Warm Teachers Make Enthusiastic Students: How Teachers Build Positive Relationships With Students - Rosyidah, Fairuz Syifa; Rifameutia, Tjut; Djoumoi, Ahmed (Jurnal Ilmu Pendidikan, 2024)
In addition to their teaching responsibilities, teachers must possess social competence, particularly in interacting effectively with their students. Previous research highlights a significant correlation between the quality of teacher-student relationships and the level of conflict within the classroom. Therefore, teacher competence in fostering positive relationships with students is essential for creating an environment of positive discipline. This research aims to enhance teachers' understanding of the fundamental principles of positive relationships through a training program titled "Warm Teachers Make Enthusiastic Students." The findings demonstrate an improvement in teachers' knowledge concerning the foundational principles of positive relationships, including encouragement, a focus on solutions, and a balanced approach of kindness and firmness. However, there was no observed increase in knowledge about the importance of caring among the teachers. The study also includes a qualitative analysis of teacher behaviors during the training sessions. It provides insights into how teachers applied the principles discussed and their overall engagement with the training material. This analysis underscores the significance of continuous professional development in the social competence of teachers, which is vital for fostering a supportive and productive classroom environment